The Effect Of Collaborative Learning Management And Academic Engagement On Statistics Learning Outcomes With Learning Motivation As A Mediating Variable (Case Study Of Diploma-3 Office Administration Students At Pamulang University) - Edi Junaedi; Liza Nora; Andry Priharta (UNIVED Press, 2026)
This study aims to analyze the influence of collaborative learning management and academic engagement on the Statistics learning outcomes of students in the Diploma-3 Office Administration Study Program at Pamulang University, with learning motivation as a mediating variable. The study used a quantitative approach with an explanatory research approach. The sample size was 150 students, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using path analysis. The results indicate that collaborative learning management and academic engagement have a positive and significant effect on student learning motivation and learning outcomes. Furthermore, learning motivation significantly influences learning outcomes and acts as a mediating variable in the relationship between collaborative learning management and academic engagement and learning outcomes. These findings emphasize the importance of collaborative learning management and increased academic engagement in improving Statistics learning outcomes.